Magnetic-field-driven reverse martensitic transformation with multiple magneto-responsive effects by manipulating magnetic ordering in Fe-doped Co-V-Ga Heusler alloys. (1st December 2020) - Liu, Kai; Ma, Shengcan; Zhang, Yuxi; Zeng, Hai; Yu, Guang; Luo, Xiaohua; Chen, Changcai; Rehman, Sajjad Ur; Hu, Yongfeng; Zhong, Zhenchen
Abstract: Nowadays, searching for the materials with multiple magneto-functional properties and good mechanical properties is vital in various fields, such as solid-state refrigeration, magnetic actuators, magnetic sensors and intelligent/smart devices. In this work, the magnetic-field-induced metamagnetic reverse martensitic transformation (MFIRMT) from paramagnetic martensite to ferromagnetic austenite with multiple magneto-responsive effects is realized in Fe-doped Co-V-Ga Heusler alloys by manipulating the magnetic ordering. The martensitic transformation temperature T m reduces quasi-linearly with increasing Fe-content. In strikingly contrast with the Fe-free alloys, the magnetization difference (Δ M ') across martensitic transformation increases by three orders of magnitude for Fe-doped alloys. The increased Δ M ' should be ascribed to the reduction of T m, almost unchanged Curie temperature of austenite and the increased magnetic moment in the samples with higher Fe-content. The large Δ M ' provides strong driving force to realize the MFIRMT and accordingly multiple magneto-responsive effects, such as magnetocaloric, magnetoresistance and magnetostriction effects. Meanwhile, giant Vickers hardness of 518 HV and compressive strength of 1423 MPa are achieved. Multiple magneto-responsive effects with exceptional mechanical properties make these alloys great potential candidates for applications in many fields.